An Overview of Verbal Violence by Teachers on Students at High School in Kupang City - Tensi Kartini Lau; Diana Aipipidely; Feronika Ratu (Universitas Nusa Cendana, 2021)
This study aims to determine the impact of verbal violence by teachers on students at SMA Negeri Kupang. This study uses a qualitative research type. This research was conducted on three participants who were students of a state high school in Kupang City. Information about the two participants was revealed using semi-structured interviews. The sampling technique used is purposive sampling. This study uses a research instrument, namely the researcher himself. The data analysis technique used in this research is interpretative phenomological analysis. The main purpose of phenomological interpretive analysis is to identify how an individual interprets his life experience. The stages in this data analysis technique are repeated reading and taking notes, turning notes into themes, looking for relationships and grouping themes, and making reports on research results. The results of this study indicate that the three participants, namely PI, AH, KA felt the impact of verbal abuse by their teachers. All three participants felt unnoticed, cared for, and felt intimidated by their own teachers. This made the participants, PI, AH and KA feel ashamed of their classmates and other teachers and often skipped class. In addition, PI, AH and KA participants hoped that teachers would not treat other students as they did to them. This shows that verbal violence does have a psychological impact on students who experience it.